Nozzle Spacing on Sprayer Boom - Khurana, Rohinish; Singh, Shashi Kumar; Dixit, Anoop (Journal of Agricultural Engineering, 2007)
Agricultural sprayers are frequently used to spray pesticides on standing crops to avoid pest attack. Nozzles are placed on sprayer boom in such a way that the chemical is spread evenly over the plant canopy. The spacing between the nozzles on the boom of commonly used sprayers is quite speculative and not based on the type of nozzle, the discharge from the nozzle, operating pressure, height of the boom, etc. A computer program was developed to select appropriate spacing between the nozzles based on operating pressure, height, spray pattern, etc. The best-suited nozzle spacing was calculated on the basis of overlap of the spread patterns. Coefficient of Variation was calculated for the different levels of overlap of the spread patterns. Spacing for which the Coefficient of Variation was minimum was taken as the best suitable spacing for nozzles on the sprayer boom. The program was validated by using operational parameters of a Triple Action Nozzle with a hollow cone spread pattern. The nozzle was operated at working pressure of 4.0 kg/cmÂ², at a height of 40 cm moving at the forward speed of 2.5 km/h. The best spacing was found to be around 57 cm. The program was also used to find out the number of nozzles required for a given boom length and the total volume of chemical sprayed per hectare.